A comprehensive proposal for rehabilitation of historic Armenian church belonging to 16th century AD (Diyarbakır, Turkey). (April 2023) - Korkmaz, Nimet Gökçe; Korkmaz, Nail Mahir; Sayin, Baris; Uzdil, Oguz
Abstract: This study presents a comprehensive proposal for the rehabilitation of the ruined Surp Sargis Church located inside the historical city walls of Diyarbakır, namely the Suriçi region. The Suriçi region was home to many ancient civilizations and cultures. This study consists of four major stages; historical research, determination of the original structural features, seismic performance assessment, and a comprehensive proposal for the rehabilitation of the building. In the first stage, the history of the church, from its construction date to the present was examined based on the historical documents, common typology of the period, and old photographs. In the second stage, the plan, facade characteristics, construction system, and material properties of the existing structure were determined and reasons for the deterioration were identified. To determine the architectural features of the analyzed church, other Armenian churches dating back to the 16th century were evaluated in addition to the examination of the old plans, photographs, and repairs. Then, in the third stage, a seismic risk assessment of the church was done through linear, pushover, and kinematic limit analyses. In the final stage, a rehabilitation proposal was presented evaluating all the data obtained from previous stages. The proposed rehabilitation practice also considered local people living around this structure. The main goal of this study is to turn this structure into an active church for religious tourism activities where Armenians living in other places can attend worship and meetings at certain times of the year. Moreover, a social activity area for local people in the surrounding region was also planned. Accordingly, the current paper provides a comprehensive rehabilitation approach that can be applied to similar cultural heritage structures.